Computational Fluid Dynamics Simulation of Clearance Effect in High Solid Loading Polydisperse Solid-Liquid Mixing - Iman Mukhaimin; Tantular Nurtono; Sugeng Winardi (Institut Teknologi Sepuluh Nopember, 2017)
A high solid loading concentration of solid-liquid mixing was investigated to observe the effect of ratio C, Clearance, and T, diameter tank, with C/T 0.33; C/T 0.25 and C/T 0.17 on local volume of hydrodynamic and spatial distribution of polydisperse solid suspension using CFD, Computational Fluid Dynamics. The 45o pitch blade turbine, diameter 0.5T, with down pumping flow simulation was used to remove solid particle from bottom of the tank. The tank is also equipped with four baffle with the size of 0.1T.. A solid-liquid mixing consists of five fractions of glass beads with equal proportion (X1=X2=X3=X4=X5=0.2X) have 40% wt total solid concentration with liquid fraction is aqueous solution of NaCl. The effect of ratio C/T at impeller speed 612 rpm create a flow pattern in the tank different. Effect ratio C / T also indicated the distribution on solid had a good uniformity index when N≥ Njs, just suspended speed. The highest uniformity was obtained on C/T 0.17. it also made difference power consumption on each geometry with C/T 0.17, 0.25, and 0.33 respectively are 251.18, 238.13, and 270.65watt.